(untitled) (Journal of Asian Development Studies, 2025)
Working memory decline with increasing age has been widely researched, yet there is minimal evidence from Pakistan. This gap highlights the need to examine working memory performance in a Pakistani context, focusing on the three domains: short-term storage, attention, and executive control. The present study compared these domains across young adulthood (19 to 40 years), older adulthood (41 to 64 years), and mature adulthood (65 years and above). A cross-sectional correlational design was used, and 277 individuals were approached, of whom 223 completed the questionnaire. The 30-item Working Memory Questionnaire, developed by Vallat-Azouv et al. (2012), rated on a 1–6 Likert scale, was administered to assess short-term storage, attention, and executive control. Results showed significant positive correlations among all three domains. ANOVA findings indicated that young adults scored lowest across all domains, followed by older adults. In contrast, mature adults scored highest, suggesting poorer working memory, as higher scores reflect greater cognitive difficulty, which means young adults possess significantly better working memory than older and mature adults. Women outperformed men across all domains, demonstrating better attention, short-term storage, and executive control. These findings confirm that age-related working memory decline is consistent within the Pakistani cohort and highlight meaningful gender differences. Limitations, cultural implications, and recommendations, including the need for future studies to ensure equal numbers of men and women, are provided.